Psychological empowerment and service orientation: A study of front-line employees in the food and beverage industry. Issue 3 (26th May 2016) - Yen, Chia-Dai; Yeh, Ching-Hui; Lin, Shin-Yi
ABSTRACT: Employees with service orientations can achieve higher service performance and create a competitive advantage for a company. The service process in the food and beverage industry is delivered by front-line employees who wield considerable authority in dealing with customers' special requests and demands. Psychological empowerment is recognized as employee feelings of empowerment and is able to elevate employees' self-recognition in the work place, improve efficiency, and increase employee self-respect. This could be an important antecedent of service orientations. This study aimed to explore employees' demographic characteristics and psychological empowerment as the antecedent factors of service orientations in the food and beverage industry.